A survey on the use of topical steroids in patients treated for lichen sclerosus-associated vulval squamous cell carcinoma. (17th February 2018) - Pounds, Rachel; Tahir, Sanna; Dawson, Christopher; Woodman, Ciaran; Luesley, David; Yap, Jason
Abstract: Evidence suggests that lichen sclerosus (LS) is the primary aetiological factor for local vulval recurrence (LVR) in vulval squamous cell carcinoma (VSCC). The long-term application of topical corticosteroids is believed to prevent LVR. Patients treated for LS-associated VSCC at a gynaecological cancer centre were invited to complete a questionnaire to evaluate whether they are receiving corticosteroids. 55 of the 95 eligible patients (58%) completed the questionnaire; LS was treated in 69%, with steroids given to 84.2%. Most received steroids >3 months, but discontinued treatment once asymptomatic. An online survey was distributed to 313 British Gynaecological Cancer Society members to determine whether gynaecological oncologists prescribe corticosteroids for LS following VSCC surgery. 41 consultants (13.1%) completed the survey; 70.7% prescribe topical corticosteroids (potent/very potent in 79.3%), and 58.6% treat >1 year. Our findings demonstrate that patients are more likely to be given topical corticosteroids if symptomatic of LS. Furthermore, although treatment regimens vary, the majority of respondents advocate the use of very potent steroids and would support a tertiary chemopreventative trial. Impact statement: What is already known on this subject: Local vulval recurrence (LVR) affects approximately one in four women who have received surgery for vulval squamous cell carcinoma (VSCC). What the results of this study add: Lichen sclerosus (LS), an inflammatory dermatosis, is recognised as the likely primary aetiological factor for LVR. Although there is evidence to suggest that long-term topical corticosteroid use in patients with residual LS may prevent LVR, the extent to which women were given topical steroids following surgery remains unclear. Our patient questionnaire evaluates if these patients are already receiving topical steroids, along with the strength of such steroids and duration of treatment. The consultant survey determines whether clinicians currently prescribe topical steroids following VSCC surgery, as well as the strength and duration of steroid therapy. What the implications are of these findings for clinical practice and/or further research: We aim to establish whether the gynaecological oncology community believe that long-term steroids may prevent LVR in women with LS-associated VSCC and whether they would support and recruit to a multicentre tertiary chemopreventative trial. These findings could influence a future clinical trial and may alter the ongoing management of these women.